A Watershed Event: Communicating Landscape Processes - JeanMarie Hartman; Donna Webb (Fábos Conference on Landscape and Greenway Planning, 2013)
A watershed event was created to illustrate and quantify how water from precipitation moves across a land surface. This illustration is one of many that would be useful in developing the environmental literacy of greenway and open space supporters. The physical activity of marking the small sub-watersheds generated discussion and collaboration between volunteers. Stopping to watch the occasion of water shedding created a notable event. The materials assembled for documenting the event have provided materials for website presentation and lectures. The basic process is fairly easy to organize and recommended for use by greenway and open space groups who are interested in this type of combined environmental art/ outreach education event.
Keywords: greenways; watershed; communication; education; landscape; processes